2020
DOI: 10.1136/bmjgh-2020-003747
|View full text |Cite
|
Sign up to set email alerts
|

Mortality surveillance and verbal autopsy strategies: experiences, challenges and lessons learnt in Papua New Guinea

Abstract: Full notification of deaths and compilation of good quality cause of death data are core, sequential and essential components of a functional civil registration and vital statistics (CRVS) system. In collaboration with the Government of Papua New Guinea (PNG), trial mortality surveillance activities were established at sites in Alotau District in Milne Bay Province, Tambul-Nebilyer District in Western Highlands Province and Talasea District in West New Britain Province.Provincial Health Authorities trialled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We have supported trials of several strategies to increase notification, including incentivising notification agents at the ward level to inform health centres about deaths in PNG. [10] Many of the challenges are related to extremely remote and hard-to-reach locations but the notification and VA teams endeavoured to visit and support collection of VAs from the majority of local government areas across the study sites. Whilst it would be preferable to achieve full death notification, the estimated completeness in this study, from a broad geographical area of each district, is expected to be adequate to estimate mortality fractions, particularly for broad cause groupings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have supported trials of several strategies to increase notification, including incentivising notification agents at the ward level to inform health centres about deaths in PNG. [10] Many of the challenges are related to extremely remote and hard-to-reach locations but the notification and VA teams endeavoured to visit and support collection of VAs from the majority of local government areas across the study sites. Whilst it would be preferable to achieve full death notification, the estimated completeness in this study, from a broad geographical area of each district, is expected to be adequate to estimate mortality fractions, particularly for broad cause groupings.…”
Section: Discussionmentioning
confidence: 99%
“…Notification of community deaths, the prerequisite for obtaining cause of death data through VA, is a particular challenge in rural areas of both Solomon Islands and PNG, and we have supported pilot strategies using different notification agents and data systems. [ 9 , 10 ] The notification systems trialled in PNG required the notification agent, usually a ward recorder or village health volunteer, to inform the nearest health centre of deaths in their designated area, using paper forms or electronic methods. Receipt of death notifications at the health centre was the trigger for health workers to organise community visits during which they would validate the notification data and enter it in a tablet computer, as well as conduct the VA interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple notification strategies in PNG included trials of paper and electronic methods and engaging different cadres of notification agent. 22 A key recommendation in both PNG and Myanmar was to identify a community reporting agent tasked with alerting relevant authorities about deaths. 23 In the Solomon Islands, three death notification strategies were piloted, using religious leaders, cemetery administrators and primary health staff as notifying agents.…”
Section: Design and Operational Issuesmentioning
confidence: 99%
“…‘Old age’ is also commonly referred to as a COD in communities. Lessons learnt with implementing mortality surveillance activities in PNG suggested that logistical arrangements and incentives should be considered as strategies to maximise completeness of mortality data, and health workers have great potential to improve the completeness of death registration in PNG 14…”
Section: Introductionmentioning
confidence: 99%